2011
DOI: 10.1016/j.bpj.2010.12.3711
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies of Ion Permeation in VDAC

Abstract: The voltage-dependent anion channel (VDAC) in the outer membrane of mitochondria serves an essential role in the transport of metabolites and electrolytes between the cell matrix and mitochondria. To examine its structure, dynamics, and the mechanisms underlying its electrophysiological properties, we performed a total of 1.77 μs molecular dynamics simulations of human VDAC isoform 1 in DOPE/DOPC mixed bilayers in 1 M KCl solution with transmembrane potentials of 0, ±25, ±50, ±75, and ±100 mV. The calculated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
93
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 46 publications
12
93
0
Order By: Relevance
“…The second (Fe B-2 ) is near the cytosolic surface, where it is coordinated by D34 and E66. These observations, which provide the first experimental evidence of Fe ions in B-pores, strongly support the idea derived from our MD simulations (51) that iron traffics across the Bfr shell using B-pores as conduits.…”
Section: Resultssupporting
confidence: 89%
“…The second (Fe B-2 ) is near the cytosolic surface, where it is coordinated by D34 and E66. These observations, which provide the first experimental evidence of Fe ions in B-pores, strongly support the idea derived from our MD simulations (51) that iron traffics across the Bfr shell using B-pores as conduits.…”
Section: Resultssupporting
confidence: 89%
“…Our findings corroborate recent MD simulations showing that E73 causes bending and water penetration into the membrane when charged (Villinger et al, 2010). However, simulations have not reported deprotonation of K110 (Choudhary et al, 2014; Noskov et al, 2013; Rui et al, 2011; Villinger et al, 2010) potentially due to electrostatic compensation due to snorkeling into the headgroups.…”
Section: Resultsmentioning
confidence: 99%
“…The physiological purpose of the ion dependence of the VDAC conductivity was theoretically addressed by Brownian and molecular dynamics simulations and essentially confirmed the experimental results on mammalian VDAC1 . For example, these studies showed that the free energy barrier prevents K + from entering or leaving the pore, whereas passage of Cl -is unhindered, when the pore is in the open state Rui et al, 2011). The hampered K + flux apparently depends on repulsive interactions between K + and a number of amino acid residues (D15, K19, D30, K61 and K95) within the barrel pore .…”
Section: Ion Conductance By Vdacsmentioning
confidence: 98%